Modelling and active damping of powertrain oscillations for RWD electric vehicle. (2017) - Lin, Cheng; Sun, Shengxiong; Jiang, Wenfei
With the promotion and popularisation of electric vehicles, their driving performance has become an increasingly important issue. As there is no clutch in the powertrain to buffer and absorb the torsional vibrations, vehicle speed oscillations will be caused by various elastic components when the accelerator pedal is stepped or shifted by the driver suddenly. The sudden acceleration input will bring an unpleasant jerk to the vehicle body and accelerates the wear and tear of various parts in the powertrain. In this paper, considering the structure of full electric vehicle, a dynamic model of the powertrain is developed. An optimal feedback controller is proposed based on the state space equation of the vehicle to prevent the driveline from oscillating by actively controlling the motor output torque. The controller parameters are designed based on the optimal control theory. Simulation results demonstrate that the optimal control of motor output torque can reduce the wheel speed oscillations significantly.